The Application of a Problem Based Learning (PBL) Model to Increase Motivation and Learning Outcomes of Class VII Students - Sisca Lusianna Sirait; Arifin, Yusna (Journal of General Education Science, 2024)
Motivation is one of the factors that influences student success. A person will get the desired results in learning if within him there is a desire to learn. Motivation as the main factor in learning functions to create something fundamental to drive learning actions. In helping children improve their learning achievements, educators, especially teachers, must create a climate that stimulates children's creative thinking and skills at school. Factors that influence the learning process are internal factors originating from students or external factors originating from outside within students. Research findings show low student learning motivation, including the following: 1) Teachers' teaching methods and methods are monotonous and unpleasant, 2) Students' economic and socio-cultural background, 3) Most students from weak economic backgrounds do not have strong motivation to study and continue their education to a higher level. 4) Advances in technology and information, 5) Feeling inadequate in certain subjects, such as mathematics and English and 6) Students' personal problems with parents, friends and the surrounding environment. This research aims to determine the effect of learning motivation on student learning achievement in the Integrated Social Sciences subject, Economics class VII. Researchers as teachers apply the problem-based learning (PBL) model in an effort to increase the learning motivation of class VII students.